Gestational exposure to perfluoroalkyl substances and congenital heart defects: A nested case-control pilot study. (September 2021) - Ou, Yanqiu; Zeng, Xiaowen; Lin, Shao; Bloom, Michael S.; Han, Fengzhen; Xiao, Xiaohua; Wang, Hui; Matala, Rosemary; Li, Xiaohong; Qu, Yanji; Nie, Zhiqiang; Dong, Guanghui; et al.
Highlights: First study of congenital heart defects (CHDs) association with PFAS in maternal and cord blood. Higher levels of maternal PFAS exposure were associated with higher odds of CHDs. The association is specifically significant in septal and conotuncal defects. Abstract: Background: Accumulating evidence suggests that environmental pollutants may contribute to the occurrence of congenital heart defects (CHDs). However, no previous studies have evaluated the impact of perfluoroalkyl substances (PFAS), persistent environmental pollutants, on CHDs. This exploratory study aimed to generate testable hypotheses of the association between gestational PFAS and the risk of CHDs. Methods: A nested case-control study was conducted in a cohort of 11, 578 newborns. Exposure odds ratios were compared between 158 CHD cases and 158 non-malformed controls delivered at the same hospital, individually matched by maternal age (±5 years) and parity. Concentrations of 27 PFAS, including linear and branched isomers, were determined in maternal peripheral blood and cord blood plasma collected before and during delivery using a ultra-performance liquid chromatography coupled to mass spectrometry. Conditional logistic regression was utilized to evaluate associations between individual PFAS and the risk of CHDs, adjusted for confounding variables. Results: Maternal gestational exposure to the highly branched perfluorooctanesulfonate (PFOS) isomer potassium 6-trifluoromethyperfluoroheptanesulfonate [6 m-PFOS, adjusted odds ratio (aOR) (95% CI) = 2.47(1.05, 5.83)] and perfluorodecanoic acid [PFDA, aOR (95% CI) = 2.33(1.00, 5.45)] were associated with increased odds of septal defects with statistical significance, while linear PFOS [aOR (95% CI) = 3.65(1.09, 12.16)] and perfluoro-n-dodecanoic acid [PFDoA, aOR (95% CI) = 6.82(1.75, 26.61)] were associated with conotruncal defects. Effect estimates also suggested associations for higher maternal 6 m-PFOS and PFDA concentrations with ventricular septal defect. However, we did not observe these associations in cord blood. Conclusion: These exploratory findings suggested that gestational exposure to most PFAS, especially linear PFOS, 6 m-PFOS, PFDA, and PFDoA, was associated with greater risks for septal and conotruncal defects. However, a larger, adequately powered study is needed to confirm our findings, and to more comprehensively investigate the potential teratogenic effects of other more recently introduced PFAS, and on associations with individual CHD subtypes.